Kształtowanie się gwarancji własności jako instytucji w niemieckim porządku konstytucyjnym - Romanowski, Marcin (Kwartalnik Prawa Publicznego, 2012)
The article describes the genesis of the contemporary shape of a guarantee of ownership in art. 14 of the German Basic Law (Constitution). It goes back to the beginning of their immediate roots in the Constitution of the Weimar Republic and debates about the determinants of its legal form. Contemporary fundamental right of ownership – in contrast to the pre-war period – guarantees the status quo of the owner in the sphere of property (Bestandsgarantie), but not only the value of his assets. It also formulates the requirement of a legal institution that deserves to be called a guarantee of private property (Institutsgarantie). Even if it does not contain specific orders of redistributing its subjects, some guidance for policy of the ownership can be derived from art. 14. The article shows the development of the fundamental right of ownership on the way of deviating from the classical concept of right of ownership applicable in civil law. A clear departure in the judgment called Naßauskiesungsbeschluß is not interpreted as a breakthrough, but as the ordering of legal discourse in accordance with the principle of hierarchy of rules in the legal system, in which constitutional rules can limit institutions of private law, regulated in the German Civil Code. In the described jurisprudence of the German Constitutional Court the content of this law is presented in detail, even though it has been shaped dynamically, by adjusting the human good to the general requirements of the common good.